The Therapeutic Efficacy of Curcumin vs. Metformin in Modulating the Gut Microbiota in NAFLD Rats: A Comparative Study - Li, Ruifang; Yao, Yurong; Gao, Pengfei; Bu, Shurui (Frontiers in Microbiology, 2021)
Abstract: Structural disruption of gut microbiota is closely related to the occurrence of non-alcoholic fatty liver disease (NAFLD). Previous research has demonstrated that both curcumin (CUR) and metformin (MET) have a therapeutic effect against NAFLD and play a role in modulating the gut microbiota. However, there is a lack of direct comparison between the two medications in terms of the therapeutic efficacy and the regulatory effect on gut microbiota. In this study, we administered either CUR or MET to rats with high-fat diet (HFD)-induced obesity to observe changes in body parameters, biochemical parameters, liver and ileum pathology and gut microbiota, and used next generation sequencing and multivariate analysis to evaluate the structural changes of gut microbiota in a NAFLD rat model before and after CUR and MET intervention. It was found that both CUR and MET attenuated hepatic ectopic fat deposition, alleviated inflammatory factors, and improved intestinal barrier integrity in HFD-fed rats. More importantly, CUR and MET reduced the Firmicutes/Bacteroidetes ratio and reverted the composition of the HFD-disrupted gut microbiota. Both CUR and MET treatments effectively modified the gut microbiome, enriched the abundance of beneficial bacteria and reduced opportunistic pathogens in obese rats. The abundance of Butyricicoccus was increased while the abundance of Dorea was decreased in HFD+CUR group. Besides, some beneficial bacteria such as Prevotella were increased in MET-treated animals. Spearman’s correlation analysis showed that Helicobacter, Akkermansia, Desulfovibrio, Romboutsia, Corynebacterium, Lactobacillus, Ruminococcaceae_unclassified, Lachnospiraceae_unclassified and Clostridiales_unclassified showed significantly positive correlations with TG, TC, LDL-C, GLU，IL-6, IL-1β and TNF-α, and negative correlations with HDL-C (both p < 0.05). However, Prevotella and Stomatobaculum showed an opposite trend. In summary, CUR and MET showed similar effects in alleviating hepatic steatosis, improving intestinal barrier integrity and modulating gut microbiota in HFD-induced obesity rats, and therefore may prove to be a novel adjunctive therapy for NAFLD.